Decomposition of skew-morphisms of cyclic groups - Kovács, István (Ars mathematica contemporanea, 2011)
A skew-morphism of a group ?$H$? is a permutation ?$σ$? of its elements fixing the identity such that for every ?$x, y \in H$? there exists an integer ?$k$? such that ?$σ (xy) = σ (x)σ k(y)$?. It follows that group automorphisms are particular skew-morphisms. Skew-morphisms appear naturally in investigations of maps on surfaces with high degree of symmetry, namely, they are closely related to regular Cayley maps and to regular embeddings of the complete bipartite graphs. The aim of this paper is to investigate skew-morphisms of cyclic groups in the context of the associated Schur rings. We prove the following decomposition theorem about skew-morphisms of cyclic groups ?$\mathbb Z_n$?: if ?$n = n_{1}n_{2}$? such that ?$(n_{1}n_{2}) = 1$?, and ?$(n_{1}, φ (n_{2})) = (φ (n_{1}), n_{2}) = 1$? (?$φ$? denotes Euler's function) then all skew-morphisms ?$σ$? of ?$\mathbb Z_n$? are obtained as ?$σ = σ_1 × σ_2$?, where ?$σ_i$? are skew-morphisms of ?$\mathbb Z_{n_i}, \; i = 1, 2$?. As a consequence we obtain the following result: All skew-morphisms of ?$\mathbb Z_n$? are automorphisms of ?$\mathbb Z_n$? if and only if ?$n = 4$? or ?$(n, φ(n)) = 1$?.
Keywords: ciklična grupa; cyclic group; permutacijska grupa; permutation group; poševni morfizem; Schur ring; Schurov kolobar; skew-morphism